Knowledge management framework linkage for cardiothoracic healthcare - A. Jabar, Marzanah; Sidi, Fatimah; Abdullah, Salfarina; O'Abdela, Nahel (2014)
Cardiovascular diseases (CVDs), the number one cause of death globally, are of disorders related to the heart and blood vessels. In 2011, the World Health Organization reported that 80% of CVD deaths occur in low- and middle-income countries. Cardiothoracic patients in hospitals need to be monitored at different point-of-care, throughout their treatment procedures which generate vast amounts of clinical data that is highly complex, multi-dimensional, unstructured and multi-modal. These clinical data are represented in different formats and stored in heterogeneous digital platforms, while some others are still recorded on paper. Thus, medical practitioners cannot effectively integrate, apply and manipulate these data into knowledge for strategic clinical decision. Although there are some frameworks focuses on how health organizations manage their knowledge, they are still different in some aspects. In order to accelerate the research progress in knowledge management, it is time to review these models in detail and integrate them into a comprehensive framework to serve as a foundation for the research. The main objective of this research is to have a holistic view of these clinical information, in a streamline processes by proposing a generic work process framework for cardiothoracic clinical research at point-of-care settings.